PENGARUH STRUKTUR AKTIVA DAN LIKUIDITAS TERHADAP STRUKTUR MODAL DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN CONSUMER NON CYCLICAL TAHUN 2018-2022 - Pardosi, Yuliana Cristine; Martono, Adi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2023)
The impact of the Covid 19 pandemic has forced companies to sell their assets as an alternative funding source to improve their capital structure and company performance. This is interesting to study because the phenomenon that occurs is that several companies carry out this strategy. This study aims to see whether changes in asset structure and liquidity to the company's capital structure, which are moderated by institutional ownership will have a positive effect. This study uses a quantitative method, sourced from secondary data, namely companies listed on the Indonesia Stock Exchange in the non-cyclical consumer industry sector for the 2018-2022 period. Companies included in this sector are companies that produce and sell products needed by the community. The data processing technique is multiple linear regression with a moderating factor. The results of this study are that the asset structure has no effect on the company's capital structure, while liquidity has a negative effect on the capital structure. The influence of asset structure on the capital structure is moderated negatively by institutional ownership, however, the effect of liquidity on the capital structure is not moderated by institutional ownership.